Are Good Companies Good Stocks? Evidence from Nairobi Stock Exchange - Ndegwa, James N.; Mboya, Josephat K. (European Journal of Business and Management, 2013)
The search for abnormal stock returns seems elusive for many investors in efficient markets unless there are anomalies in such markets. This has led to the development of numerous stock selection methods including the application of technical and fundamental analysis in an attempt to beat the market. There is uncertainty as to whether good companies that are defined by strong earnings and sales growth are also good stocks whose prices appreciate and outperform other stocks in the market. This research employs a study sample consisting of 32 companies listed in the NSE to establish the relationship between good companies and good stocks. The Pearson’s correlation coefficient and descriptive statistics techniques were employed. The results indicate that there is a strong positive correlation between the good companies and good stocks in the NSE.